DESIGN & IMPLEMENTATION OF SMART GRID USING CELLULAR NETWORKS AS ITS AMI BACKBONE - Abdul Rehman; Kiran Raheel; Khalid Rehman; Ali Mujtaba Durrani; Muhammad Yaseen; Aman Obaid; Muhammad Imran; Abdul Aziz; Romaisa Shamshad Khan (Spectrum of Engineering Sciences, 2025)
To solve the limitations of current power grid, Smart Grid is the solution. Its backbone is AMI (Advanced Metering Infrastructure), but its major problem is lack of unified data transmission infrastructure within the grids which should able to send big amount of data collected from each smart meter of a town or city to the center in cheap and secure way. In the current design of AMI in SG needs the implementation of a separate/mix transmission data infrastructure which will have very high cost. So, we introduce the use of Cellular networks in transmitting consumer data (usage and controlling) to the center and vice versa. We have designed a system where smart meters equipped with Cellular SIM Cards and Wi- Fi technologies communicate directly with the Hub in a secure way, bypassing the need for extensive infrastructure. The Wi-Fi in smart meters will be used in IoT of customer's home equipment management. This system could be deployed in the whole country just by installing smart meters and renting Cellular Companies Transmission infrastructure to send each customer data to the Hub. This design has been simulated in MATLAB. So, this approach associated with low-cost, high security and easy maintenance as the Cellular network's companies will be responsible for its maintenance just like their new cellular sites. This re-search provides a blueprint for utility companies and policymakers to upgrade electricity systems economically and efficiently using/renting already installed Cellular infrastructure.